La promocion de nueva actividad terciaria en la ciudad de Barcelona - Benach, Nuria (1994)
THE PROMOTION OF NEW TERTIARY ACTIVITIES IN BARCELONA - The profound extent of the recent transformation of cities can be analysed through the changes shown in urban patterns and urban functions, as well as through their relationship with new ways of urban planning. This article begins by evaluating the extent of the tertiary sector in Barcelona through the development of several macroeconomical indicators. Then we study the centralising tendency in the location of certain tertiary activities, especially those involved in decision and management, and those of the recently growing producer services. Afterwards we look at tertiary activities relevance as an instrument of urban politics in general, and in the case of Barcelona, in particular. Finally, we foresee the situation of certain branches with major potencial growth such as tourism, health or financial services.